Plan estratégico para la clínica veterinaria Stuart en la ciudad de Tunja, Boyacá (2022)
The objective of this work is to propose a strategic plan for the Stuart Veterinary Clinic; which provides medical care, nursery, beauty and Petshop services, for which an internal and external diagnosis of the company was carried out using the DOFA matrix anda stratified survey of clinic clients.